PLANNING TRAINING SESSIONS FOR THE DEVELOPMENT OF SPEED-STRENGTH QUALITIES IN FOOTBALL PLAYERS (Scientific journal of the Fergana State University, 2026)
The article analyzes the process of training young football players and the methodological foundations for developing their physical, technical-tactical, and psychological readiness. The preparation of football players is carried out in two stages — general and special training. During the general training stage, physical endurance, technical skills, and tactical abilities are developed, while the special training stage focuses on football-specific qualities and enhancing performance in the game. Additionally, methods for planning training sessions, monitoring, and assessing players’ readiness during competitions are examined. The results of the study confirm the importance of a methodological approach for the effective training of young football players and improving their competitive performance.